Succession politics and state administration in Africa: the case of Zimbabwe - Arthur Fidelis Chikerema; Ogochukwu Nzewi (Electoral Institute for Sustainable Democracy in Africa, 2023)
The paper is a critical inquiry into the influence of succession politics on state administration in Africa, with particular reference to Zimbabwe, and unpacks the interactive boundaries and conceptual overlaps in this field. This study was based on 18 qualitative in-depth interviews conducted with key informants using the purposive sampling technique, complemented by extensive document review. The findings of the study show that succession politics in Africa includes executive dominance, egocentrism and excessive appointive powers. These are compounded by the lack of an institutional framework of succession, which in turn undermines the professional independence of the bureaucracy and inhibits the pursuit of comprehensive governance. The findings also isolate Zimbabwe as a victim of political, societal and historical factors that exacerbate the succession dilemma. In its recommendations, the paper argues that the succession challenge faced by the continent, in particular Zimbabwe, will continue to hound succession trends and responsive administration unless broad-based reforms are instituted to dismantle the historical legacies embedded in the political systems.